Political reforms and the funding of parties in Japan: 1955–2020. Issue 2 (17th February 2023) - Carlson, Matthew M.; Nakabayashi, Masaki
ABSTRACT: A critical issue related to the regulation of money in politics is whether specific rules favour certain parties over others. Although reformers in Japan implemented major changes in 1975 and 1994 to reduce corruption and money-drenched elections, little is known about their relative impacts on the ability of parties to raise funds. Using party financial disclosure reports from the 1955–2020 period, we analyse the effects of the reforms on the ability of parties to collect funds. One possible interpretation is that stricter regulations helped reveal heterogeneity among parties that had existed prior to the reform, which had been latent due to the lack of strict regulations. Parties that relied on less transparent sources of funding such as the Liberal Democratic Party were more vulnerable to stringent regulations regarding contributions. We find that that the 1975 and 1994 reforms favoured opposition parties rather than the Liberal Democratic Party. This research has implications not only for the development of organized parties in Japan, but also for institutional efforts to regulate the flow of political funds and minimize their potential misuse in general.